2016
DOI: 10.1002/2016gl070373
|View full text |Cite
|
Sign up to set email alerts
|

The anomalous change in the QBO in 2015–2016

Abstract: The quasi‐biennial oscillation (QBO) is a tropical lower stratospheric, downward propagating zonal wind variation, with an average period of ~28 months. The QBO has been constantly documented since 1953. Here we describe the evolution of the QBO during the Northern Hemisphere winter of 2015–2016 using radiosonde observations and meteorological reanalyses. Normally, the QBO would show a steady downward propagation of the westerly phase. In 2015–2016, there was an anomalous upward displacement of this westerly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
199
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(220 citation statements)
references
References 17 publications
16
199
1
Order By: Relevance
“…A crucial test of our understanding and ability to model the QBO occurred around the beginning of 2016 when the QBO cycle was unexpectedly disrupted for the first time since its discovery in the late 1950s (Dunkerton, 2016;Newman et al, 2016;Osprey et al, 2016;Coy et al, 2017). The well-established QBO paradigm, originating from the 1960s, of alternate eastward and westward momentum deposition from vertically propagating equatorial waves (Baldwin et al, 2001) could not account for this disruption .…”
Section: Scientific Rationalementioning
confidence: 99%
“…A crucial test of our understanding and ability to model the QBO occurred around the beginning of 2016 when the QBO cycle was unexpectedly disrupted for the first time since its discovery in the late 1950s (Dunkerton, 2016;Newman et al, 2016;Osprey et al, 2016;Coy et al, 2017). The well-established QBO paradigm, originating from the 1960s, of alternate eastward and westward momentum deposition from vertically propagating equatorial waves (Baldwin et al, 2001) could not account for this disruption .…”
Section: Scientific Rationalementioning
confidence: 99%
“…The unusual disruption of the QBO in winter 2015/2016, characterized by anomalous easterly acceleration occurring in the QBO westerlies (e.g., Osprey et al, 2016;Newman et al, 2016;Coy et al, 2017), begins at approximately the same time as the unusual strong SPW amplitude takes place in the subtropical mesosphere. Osprey et al (2016) found an anomalous easterly acceleration of the equatorial winds at 40 hPa (approx.…”
Section: Why Does the Spw 2 Dominate In Period Ii?mentioning
confidence: 99%
“…Firstly, in early winter the polar vortex was the coldest and strongest it has been in 68 years (Matthias et al, 2016) with zonal mean wind speeds of over 80 m s −1 around the stratopause in midlatitudes. Secondly, a significant disruption of the quasibiennial oscillation (QBO) occurred, beginning at the end of December 2015 and fully completing by mid-April 2016 (Osprey et al, 2016;Newman et al, 2016;Coy et al, 2017). Thirdly, this particular winter was also characterized by one of the strongest El Niño events on record, with a strong polar stratospheric signature (Palmeiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the stacked easterlies/westerlies/easterlies observed at Kiritimati (Fig. 9a) and at Singapore (Newman et al 2016) are clearly 10 present in early-to mid-March 2016 (Fig. 9b), and fine-scale descending waves are evident in the lower stratosphere above about 20 km through much of the cruise (Fig.…”
Section: Soundings From Kiritimati Islandmentioning
confidence: 99%